Penerapan Model Pembelajaran Inside Outside Circle (IOC) untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Aqidah Akhlak - Karnita Sarina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to determine the effect of student activeness and learning outcomes by applying the Inside Outside Circle (IOC) learning model. This research is a Classroom Action Research conducted through two cycles. Data collection techniques were carried out at the end of the cycle using test questions, teacher and student activity observation sheets, and questionnaires. The results of the data analysis obtained showed that the application of the Inside Outside Circle (IOC) learning model could increase student activeness and enthusiasm for learning with a percentage of teacher activity in cycle I at 66% and increased to 90% in cycle II and student activity with 68% in cycle I and 93% in cycle II. The completeness of student learning outcomes in the process I obtained 74% of students who were complete while in cycle II, increased to a percentage of 88% in very high criteria with three students who still needed to be finished out of 27 students. Student response to applying the inside-outside circle (IOC) learning model in cycle I was excellent, with an overall percentage of 85.37%. I increased in cycle II, with a rate of 88.61%.